Systematic literature review (SLR): “Dysfunctional audit behavior Determinants on Auditors Working at Public Accounting Firm in Indonesia” - Nurlatifah, Siti; Ahmar, Nurmala (Journal Markcount Finance, 2024)
This study aims to determine the main factors that influence dysfunctional audit behavior. The method used in this study is the literature review (SLR) method. The survey was conducted on previous studies whose research objects were Auditors at Public Accounting Firms in Indonesia. The research data was obtained from journals in Google Scholar on the website https://google.scholar/ in 2018-2022. The main findings of this study found that the most influential factors (determinants) in dysfunctional audit behavior were dysfunctional audit behavior, namely time budget pressure, locus of control, task complexity and rotation intention, auditor performance, and personal character. Auditor performance, Machiavellian, moral competence (Akhlaq Al Karimah), Spiritual Intelligence, Stress at work, Furthermore, future research must also consider the need to explore, reflect and ask questions more critically, not from the foregone side. For example, ask again how Public Accounting Firm leaders conduct performance assessments to reduce dysfunctional auditor behavior.